Towards Sustainable Additive Manufacturing: Exploring Ecofriendly Materials for Green 3D Printing - Kumar S Vinod; Reddy Uma; Nagpal Amandeep; Kumar Ashwani; Jayronia Sonali; Hussien Raghad Ahmed (E3S Web of Conferences, 2024)
The area of additive manufacturing, usually referred to as 3D printing, has recently experienced major growth and advancement, leading to dramatic changes across different industries like as healthcare and aerospace. But the issue of environmental sustainability remains to be of extreme significance, considering the significant utilization of resources and production of waste that relates to conventional 3D printing materials and methods. The objective of this research study is to examine the potential and efficacy of environmentally friendly materials in the wider context of 3D printing. This study examines recent advances in sustainable materials, with a focus on analysing their environmental effects, efficacy, and feasibility comparative to conventional equivalent. The research also investigates the implementation of environmentally friendly techniques within the method of additive manufacturing, covering aspects such as obtaining of materials, energy usage, and management of waste. The results of our investigation indicate that making use of environmentally friendly materials, combined with green production techniques, has the potential to considerably decrease the ecological impact of 3D printing. This progress holds promise for furthering the sustainability of additive manufacturing and designing a more sustainable future.